An investigation into the representations of environmental issues relating to Lake Victoria, Uganda, and their negotiation by the lakeside communities,An exploration of how CBS radio represents and constructs environmental issues relating to Lake Victoria, Uganda, and the negotiation of the radio programmes by lakeside communities - Lwanga, Margaret Jjuuko Nassuna (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2013)
The state of the environment is increasingly present as an urgent concern for contemporary political, social, cultural and physical life. Yet the roles of the mass media (radio, television and newspapers) in shaping and influencing crucial public awareness, debates and environmental decision-making remain inadequately understood. Positioned as a critical studies inquiry into media representations and audience reception, this study forms part of a wider project amongst media scholars and culture critics on the relationship between media textual production and consumption. It explores how one radio station in Uganda, Central Broadcasting Service (CBS) radio, represents and constructs the environmental crises faced by Lake Victoria, especially pollution and overfishing. The focus is on the Victoria Voice radio documentaries aired on CBS radio in the year 2005. The study further explores how three lakeside communities negotiate these issues as radio broadcasts. It recognises that while the mass media contribute significantly to creating public awareness about such social concerns, their likelihood of having a direct and predictable impact on social behaviour is slight. The context and the lived experiences at the reception stage where the decisions are made on whether to adopt an innovation are ultimately the factors which impact on how they are negotiated. The thesis is informed by the theoretical and analytical framework of Cultural Studies as well as the Participatory Approach to Communication for Development perspectives. The study is specifically informed by the theories of 'discourse' (Foucault, 1980a, 1981) and the 'circuit of culture' (du Gay et al., 1997 and Johnson, 1987) and these provided the conceptual framework for investigating the representations, the production and the consumption of media texts. Predominantly qualitative methods have been employed in data collection and analysis. In the first place, a Critical Discourse Analysis (CDA) (Fairclough, 1995a, 1995c) of the radio texts has interrogated the discourses and discursive practices of CBS' Victoria Voice environmental radio programmes in order to consider its representations of particular issues and consequently the discourses it privileged. Qualitative methods of participant observation, in-depth interviews and focus group discussions were deployed to investigate the negotiation of the texts by the lakeside communities. This research establishes that the Victoria Voice radio texts foreground three contesting types of discourses: the discourse of basic economic survival and livelihoods is articulated largely by the ordinary people, the lakeside communities; the discourse of sustainable development, particularly the protection and sustainability of Lake Victoria, by scientists and environmental experts; and the discourse of modernisation and corporate investment by politicians and/or policy makers and industrialists. The texts, to a large degree, reaffirm the hegemonic relations of power in Ugandan society, and thus contribute to the maintenance of the status quo. The selection of an elite category of informers (scientists, experts, politicians, policy makers) serves to marginalise the less powerful ordinary people (the fisher folk, farmers and other eyewitnesses). The construction of the elite as active and speaking subjects within the various debates introduced in these programmes, for example, works both to obscure and endorse the unequal power relations. At the reception side, while the lakeside communities attest to the relevance of the programmes in providing information on the issues concerning Lake Victoria and other aspects of their livelihood, they also recognise the power relations that underpin the sets of representations. Amongst these sets is government's complicity with industry, in line with their economic policies and the global capitalist economy, while espousing the rhetoric of nature conservation. The study argues that sustainable solutions for the crises on Lake Victoria should take into account the socio-historical and cultural contexts of the lakeside communities. For the Ugandan media, particularly radio, there is a need to rethink the nature of the coverage, which tends to neglect the contextual factors, such as local socio-economic and cultural factors within which environmental issues and problems occur and which, as this thesis establishes, greatly influences the way people make sense of environmental issues and problems. I posit that the Participatory Approach that seeks to address the communities' most pressing concerns should be adopted "“ to include more of the communities' voices and involve them in the production of radio programmes.
Keywords: Victoria; Voice; Victoria, Lake -- Environmental aspects -- Research; Lakes -- Environmental aspects -- Research -- Uganda; Environmental management -- Research -- Uganda; Pollution -- Environmental aspects -- Uganda; Radio broadcasting -- Uganda; Uganda CBS; Central Broadcasting Service; Mass media -- Environmental aspects -- Research -- Uganda